Cough during therapeutic thoracentesis: Friend or foe?. Issue 1 (3rd November 2014) - Zielinska‐Krawczyk, Monika; Michnikowski, Marcin; Grabczak, Elzbieta M.; Palko, Krzysztof J.; Korczynski, Piotr; Golczewski, Tomasz; Krenke, Rafal
<x xml:space="preserve">Abstract</x> We report intriguing preliminary observations on the effect of cough on pleural pressure changes during therapeutic thoracentesis. We found that cough‐related elevation of pleural pressure persisted even when the cough had stopped. Thus, we hypothesize that cough during therapeutic thoracentesis may have a beneficial effect preventing the excessive drop in pleural pressure. The true role of cough‐related elevation of pleural pressure is unknown, but it seems to be an interesting subject for further research.